A reassessment of the history of the temporal resolution of rainfall data at the global scale - Renato Morbidelli; Alessia Flammini; Odinakachukwu Echeta; Raffaele Albano; Gabriel Anzolin; David Zumr; Wafae Badi; Nicola Berni; Miriam Bertola; José María Bodoque; Theo Brandsma; Arianna Cauteruccio; et al. (Journal of Hydrology, 2025)

Poly(biphenyl-piperidinium)/poly(biphenyl-trifluoroacetophenone) random and block copolymers enabling highly stable anion exchange membranes for water electrolysis - Tommaso Caielli; Alessandro Raffaele Ferrari; Diego Stucchi; Chiara Ferrara; Angela Caprì; Irene Gatto; Vincenzo Baglio; Alice Pancaldi; Adele Sassella; Stefania Zappia; Alberto Giacometti Schieroni; Piercarlo Mustarelli (Chemical Engineering Journal, 2025)

Cascade sensitivity tests to model deep convective systems in complex orography with WRF - Francesco Ferrari; Enrico Maggioni; Alessandro Perotto; Raffaele Salerno; Mauro Giudici (Atmospheric Research, 2023)

Immunophenotypical characterization of paraneoplastic neurological syndrome patients: a multicentric study - Lorenzo Lorusso; Vincenza Precone; Ian K Hart; Bruno Giometto; Raffaele Pezzani; Gaelle K Ngonga; Stefano Paolacci; Daniela Ferrari; Giovanni Ricevuti; Ernie Marshall; Matteo Bertelli (Journal of Biosciences, 2021)

On the Future of Argo: A Global, Full-Depth, Multi-Disciplinary Array - Dean Roemmich; Matthew H. Alford; Hervé Claustre; Kenneth Johnson; Brian King; James Moum; Peter Oke; W. Brechner Owens; Sylvie Pouliquen; Sarah Purkey; Megan Scanderbeg; Toshio Suga; et al. (Frontiers in Marine Science, 2019)

Frontotemporal Dementia: From Mendelian Genetics Towards Genome Wide Association Studies - Raffaele Ferrari; John Hardy; Parastoo Momeni (Journal of Molecular Neuroscience, 2011)

Shutdown of turbulent convection as a new criterion for the onset of spring phytoplankton blooms - John R. Taylor; Raffaele Ferrari (Limnology and Oceanography, 2011)
The onset of phytoplankton blooms in late winter, early spring has been traditionally associated with the shoaling of the mixed layer above a critical depth. Here we show that the onset of a bloom can also be triggered by a reduction in air–sea fluxes at the end of winter. When net cooling subsides at the end of winter, turbulent mixing becomes weak, thereby increasing the residence time of phytoplankton cells in the euphotic layer and allowing a bloom to develop. The necessary change in the air–sea flux generally precedes mixed‐layer shoaling, and may provide a better indicator for the onset of the spring bloom than the mixed‐layer depth alone. Our hypothesis is supported by numerical simulations and remote sensing data.

Eddy-Mixed Layer Interactions in the Ocean - Raffaele Ferrari; Giulio Boccaletti (Oceanography, 2004)